Associations of urinary caffeine and caffeine metabolites with metabolic syndrome in US adults - Zhou, Jianli; Qin, Linyuan (Frontiers in Nutrition, 2023)
The relationship between caffeine and metabolic syndrome (MetS) has only been evaluated from the perspective of caffeine consumption. The association between urinary caffeine and MetS is still unclear. This study examined the associations between urinary caffeine and its metabolites and MetS and its components among adults. Methods: Data from the United States (US) National Health and Nutrition Examination Survey (NHANES) 2011-2014 was analyzed.NHANES is a stratified, multi-stage survey of all non-institutionalized persons in the US. A total of 2394 subjects aged ≥18 years without missing data were selected in this study. Urinary caffeine and caffeine metabolite levels were quantified using highperformance liquid chromatography-electrospray ionization-tandem quadrupole mass spectrometry (HPLC-ESI-MS/MS) with stable isotope-labeled internal standards. We performed principal components analysis (PCA) to investigate the underlying correlation structure of 15 features of urinary caffeine and its metabolites and then used these principal components (PCs) as independent variables to conduct logistic regression analysis with or without restricted cubic splines (RCS) terms to explore the associations between caffeine metabolites and MetS. Results: Two main PCs that derived from the PCA explained 90.67% of the total variance of caffeine and its